Ocena aptecznych zakazów reklamowych w świetle wartości konstytucyjnych - Sołtys, Bogusław (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This article is devoted to assessing the legitimacy of pharmacy advertising bans formulated in Pharmaceutical Law. The author carries out their legal assessment and considers their legality in the light of the collision of various constitutional values. He is inclined to conclude that the pharmacy advertising bans, by their extensive scope and abstractness, violate the guarantees of protection of constitutional rights and freedoms and are excessive in relation to the public purposes they serve. It concludes that rationing, although permissable in exceptional circumstances, should never be a shortcut in a democratic state under the rule of law.
Keywords: pharmaceutical law; advertising law; pharmacy advertising bans; rationing and its excessiveness; weighing of constitutional values